COVID-19 and Male Reproduction: A Thorny Problem. Issue 1 (February 2022) - Li, Xiaoping; Chen, Zhiqiang; Geng, Jinke; Mei, Qian; Li, Hong; Mao, Caiping; Han, Mutian
With the global epidemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the increasing number of infections, little is known about how SARS-CoV-2 affects the male reproductive system during infection or after recovery. Based on the existing research data, we reviewed the effects of SARS-CoV-2 on the male reproductive system and discussed its possible mechanism of action. SARS-CoV-2 enters host cells through the angiotensin-converting enzyme 2 (ACE2)/transmembrane serine protease 2 (TMPRSS2) pathway, and males are more susceptible than females. After infection, immunopathological damage is noticed in the testicles, and the semen index is significantly reduced. Second, abnormalities of serum follicle-stimulating hormone (FSH), luteinizing hormone (LH), and testosterone (T) levels were also observed, suggesting that there may be dysfunction of the hypothalamic–pituitary–gonadal (HPG) axis. Even after recovery, the effect of SARS-CoV-2 on the male reproductive system can last for at least a period. There are still many unresolved questions about the effect of SARS-CoV-2 infection on the male reproductive tract. Other receptors involved during the invasion of human cells by SARS-CoV-2 remain to be identified. Will the mutation of SARS-CoV-2 increase the diversity of receptors? How does SARS-CoV-2 affect the HPG axis? The long-term effects of SARS-CoV-2 on the male reproductive system remain to be evaluated. SARS-CoV-2 infection can affect male reproductive function. Standard treatment strategies should be developed in time to protect the fertility of infected patients. For recovered patients with fertility requirements, fertility assessments should be performed and professional fertility guidance should be provided at the same time.